Climatic Droplet Keratopathy in Argentina: Involvement of Environmental Agents in Its Genesis Which Would Open the Prospect for New Therapeutic Interventions. (16th September 2015) - Suárez, María Fernanda; Correa, Leandro; Crim, Nicolás; Espósito, Evangelina; Monti, Rodolfo; Urrets-Zavalía, Julio Alberto; Serra, Horacio Marcelo
Abstract : Climatic droplet keratopathy (CDK) is a degenerative corneal disease of unknown etiology. We described CDK for the first time in Latin America in the Argentinean Patagonia (El Cuy). A deeper knowledge of CDK pathogenic mechanisms will provide new therapeutic strategies. For that reason we investigated the prevalence of CDK in El Cuy and its existence in other 3 provinces with similar climate. Patients eyes were examined, habits throughout lives were inquired about, and serum ascorbate (sAA) was determined. All individuals work outdoors for most of the day. All regions had normal O3 levels. Individuals from regions 1, 2, and 3 had very low consumption of vegetables/fruits and low sAA levels. Conversely, region 4 individuals had balanced diet and higher sAA concentrations. CDK was only found in region 3 where individuals had partial deficiency of sAA and did not use eye protection. No CDK was found in regions 1 and 2 where individuals had similar work activities and dietary habits to those in region 3 but wear eye protection. No disease was found in region 4 where individuals work outdoors, have balanced diet, and use eye protection. To summarize, the CDK existence was related not only to climate but also to the dietary habits and lack of protection from sunlight.